Analisis Model Bisnis pada Kuliner Krupuk Kulit PD IKA dengan Pendekatan Business Model Canvas - Hafni Khairunnisa (Jurnal Pariwisata Indonesia, 2022)
The development of a business needs to be done to increase its capacity of a business. PD Ika is a business engaged in the culinary field, precisely the production of fish skin crackers. PD Ika needs business development to increase its business volume. The business model canvas is a tool to see how a business is developed. The research method used is qualitative using a SWOT approach to analyze the canvas business model at PD Ika. 9 (Nine) components used in general have been carried out at PD Ika. Further development needs to be carried out by taking into account the SWOT analysis that has been carried out on the customer segment and needs to target new customers. The value proposition can be improved with halal certification. Key partnerships can work with the government, academia, mass media, investors, and the community. Customer relationships using social media, websites, and other media. Channels for marketing other than offline marketing also need to use digital marketing. Improvements also need to be made on the other four elements, namely revenue stream, key activities, cost structure, and key resources.